Molecular and Cellular Mechanisms of Aldosterone Producing Adenoma Development - Boulkroun, Sheerazed; Fernandes-Rosa, Fabio Luiz; Zennaro, Maria-Christina (Frontiers in Endocrinology, 2015)
Primary aldosteronism (PA) is the most common form of secondary hypertension with an estimated prevalence of ~10% in referred patients. PA occurs as a result of a dysregulation of the normal mechanisms controlling adrenal aldosterone production. It is characterized by hypertension with low plasma renin and elevated aldosterone and often associated with hypokalemia. The two major causes of PA are unilateral aldosterone producing adenoma (APA) and bilateral adrenal hyperplasia, accounting together for ~95% of cases. In addition to the well-characterized effect of excess mineralocorticoids on blood pressure, high levels of aldosterone also have cardiovascular, renal and metabolic consequences. Hence, long-term consequences of PA include increased risk of coronary artery disease, myocardial infarction, heart failure and atrial fibrillation. Despite recent progress in the management of patients with PA, critical issues related to diagnosis, subtype differentiation and treatment of non-surgically correctable forms still persist. A better understanding of the pathogenic mechanisms of the disease should lead to the identification of more reliable diagnostic and prognostic biomarkers for a more sensitive and specific screening and new therapeutic options. In this review we will summarize our current knowledge on the molecular and cellular mechanisms of APA development. On one hand, we will discuss how various animal models have improved our understanding of the pathophysiology of excess aldosterone production. On the other hand, we will summarize the major advances made during the last few years in the genetics of APA due to transcriptomic studies and whole exome sequencing. The identification of recurrent and somatic mutations in genes coding for ion channels (KCNJ5 and CACNA1D) and ATPases (ATP1A1 and ATP2B3) allowed highlighting the central role of calcium signaling in autonomous aldosterone production by the adrenal.